Ramkheri 1955 - Jamgod 1990: Überlebensstrategien im ländlichen Indien.: Wirtschaftsgeographische Veränderungen in einer Malwa-Gemeinde - Bronger, Dirk (ERDKUNDE, 1993)
In his study of Ramkheri village in Central India from 1955 the author, A. C. MA YER, reached a rather depressing conclusion or prognosis regarding the economic perspectives in conjunction with the population growth since 1901: At present the population has levelled out around 900, which seems to be the maximum that the state of agriculture and village crafts can support (MAYER 1960, p. 20). Since then (1955) the population of this village has grown by 2.5-times. There was neither a change in the village area (1277 ha) nor any out-migration worth mentioning. Also the village crafts have not shown a recognizable development in the past 35 years. Nevertheless, the standard of living has not deteriorated at all for a remarkable number of the village inhabitants. The target of this paper is the attempt to work out the actual causes of this see singly positive development achieved not only in Ramkher by analysing the concrete living conditions, including their changes of the village inhabitants within the past 35 years (1955-1990). Regarding the agricultural sector, the improvement of the living conditions of the villagers had been achieved by the expansion of the cropped area from 680 to 1350 ha in combination with the intensification of the cultivation itself: extension of the irrigated area by 12-times since 1950, adoption of new high yielding varieties (jowar, wheat) and a radical change of cropping pattern, i.e. replacement of cotton by soybean (kharif) and wheat (rabi). The most striking result of all these changes was that the per capita wheat production alone quadrupled with the past 12 years. The analysis regarding the caste-wise participation reveals, however, that only those strata with accessibility to the groundwater resources via wells took advantage of this remarkable development: in concrete terms the share of the Rajput and Khatis (31,2% of the population) amounts to 60% of the wheat cultivation whereas the Paria castes of the Balais and Chamars (19,2 %) cultivated just 2.4 %. All in all a significant part of the village people are partly or wholly excluded from this development possibility. In addition the Paria castes particularly have lost partly (Chamar: cobbler) or completely (Balai: weaver) their caste occupation. This result of a polarized agrarian society leads to the question to what extent these disadvantaged strata have been able to develop other sources of income. Jamgod took advantage of the rural industrialization programme in conjunction with its favourable location close (12 km) to the industrial growth pole of Dewas town. The empirical caste wise analysis of all (438) households revealed that since the end of the seventies up to 1991 93 predominantly new created jobs in the secondary and tertiary sector outside and 15 inside Jamgod, besides the increase of the agricultural production, are to be considered as the main impetus for improving the standard of living of the village inhabitants. In the different programmes of both sectors almost all castes participated. This relates also to the two main Paria castes: their share amounts to 21.3 % . As far as the future perspectives are concerned, the decisive development problem of India is still to be seen in the continuous race between the population growth and the increase of productivity. The permanent sinking of the ground-water level to be observed in many regions of the country could be a serious barrier for the increase of the productivity, essential to feed a still fast-growing population also in the future. Under these circumstances the further enlargement of the labour-intensive small scale industrial sector in the rural areas must have a higher priority. Only then will the village population have the real possibility to participate in the overall development. For this Jamgod is an encouraging example.